Does FDI Attract Immigrants? An Empirical Gravity Model Approach. Issue 1 (March 2019) - Bang, James T.; MacDermott, Raymond
This study tests whether foreign direct investment (FDI) and migration are substitutes or complements using data on bilateral FDI flows from countries that are members of the Organisation for Economic Co-operation and Development (OECD) and bilateral immigration to OECD countries over the period 1996 to 2006. Our most conservative estimates, using dynamic panel methods, suggest that a $1 million increase in FDI to another OECD country increases immigration by about 60 migrants, while the same increase to non-OECD locations increases migration by about 1, 000. These findings support a core-periphery model of globalization and development.